Investigation of the influence of calibration practices on cytogenetic laboratory performance for dose estimation. (2nd January 2017) - Trompier, François; Baumann, Marion; Barrios, Lleonard; Gregoire, Eric; Abend, Michael; Ainsbury, Elizabeth; Barnard, Stephen; Barquinero, Joan Francesc; Bautista, Juan Antonio; Brzozowska, Beata; Perez-Calatayud, Jose; De Angelis, Cinzia; et al.
Abstract: Purpose: In the frame of the QA program of RENEB, an inter-laboratory comparison (ILC) of calibration sources used in biological dosimetry was achieved to investigate the influence of calibration practices and protocols on the results of the dose estimation performance as a first step to harmonization and standardization of dosimetry and irradiation practices in the European biological dosimetry network. Materials and methods: Delivered doses by irradiation facilities used by RENEB partners were determined with EPR/alanine dosimetry system. Dosimeters were irradiated in the same conditions as blood samples. A short survey was also performed to collect the information needed for the data analysis and evaluate the diversity of practices. Results: For most of partners the deviation of delivered dose from the targeted dose remains below 10%. Deviations larger than 10% were observed for five facilities out of 21. Origins of the largest discrepancies were identified. Correction actions were evaluated as satisfactory. The re-evaluation of some ILC results for the fluorescence in situ hybridization (FISH) and premature chromosome condensation (PCC) assays has been performed leading to an improvement of the overall performances. Conclusions: This work has shown the importance of dosimetry in radiobiology studies and the needs of harmonization, standardization in irradiation and dosimetry practices and educational training for biologists using ionizing radiation.